A f(R)esh take on gravity - Worsley, Jess (Department of Astronomy, 2026)
This thesis explores perturbations in f(R) modified gravity theories, with a focus on understanding the growth of large-scale structures in the Universe. Modified gravity models, particularly f(R) theories, offer an alternative explanation for cosmic acceleration without invoking dark energy. The work is divided into four key areas: foundational methods in cosmology, structure formation, perturbation theory, and the application of these methods in modified gravity models. By analysing the evolution of cosmological perturbations in these models, this research aims to provide new insights into their viability and consistency with observational data. Particular attention is given to the development of a bottom-up approach, allowing the reconstruction of gravity theories from observational constraints and bypassing the limitations of traditional model-specific methods.